Competencias parentales desarrolladas en mayor grado por los padres y madres de los niños/as y adolescentes en situación de no abandono, según mandato judicial de la Corte Superior de Justicia - La Libertad. 2015. - Mauricio Ruíz, Cinthya del Rocío (2016)
This research entitled "Parental competencies developed to a greater extent by parents of children/as and adolescents at no abandonment, according injunction of the High Court of Justice - La Libertad. 2015 ", arose from the need to know those who develop parenting skills parents family reintegration after their children /as. The stated objective is directed to investigate parental competencies developed to a greater extent by parents, grouping them into four areas: link, training, protection and reflection. Research is quantitative-qualitative and employing various methods (deductive-inductive, statistical) techniques (tests, observation, depth interview) and instruments (observation guide, interview guide, scale positive parenting) that allow collection of quantitative and qualitative data, in order to consolidate research. It was considered as units of study 12 people between fathers and mothers, who represent the families of the children/as and adolescents who have been abandoned by court order, taking into account the cases of monthly monitoring in the field of abandonment of the Third Court family Superior Court of Justice of La Libertad 2015. The results confirm that the parental competencies developed to a greater extent are the protectors and relational, because through temporary loss of their children/as, parents regained the importance of providing love and protection. In the protective parenting skills, parents are responsible for the care and meeting the basic needs of their children/as well as the receipt of their physical, emotional and psychosexual security and the relational parenting competencies, parents manifest expressions of affection to their children /as well providing a warm atmosphere to develop.